Mooreonuphis vespa, a new brooding species of Onuphidae (Annelida) from northern Spain (Bay of Biscay) - Arias, Andrés; Paxton, Hannelore; Anadón, Nuria (Zootaxa, 2013)
A new species of the genus Mooreonuphis Fauchald, 1982 collected from the Cantabrian shelf (Bay of Biscay) is described. Mooreonuphis vespa sp. nov. constitutes the first record of this genus in European waters and is characterised by: conspicuous dark brown transverse segmental pigment bands; antennae and palps with 3–5 basal ceratophoral rings and a very long distal ring; unusually long and slender peristomial and dorsal cirri; simple branchiae from chaetiger 17–19. We present observations on its reproductive biology (including brooding behaviour) and remark on the biogeography of the genus.